Staying alive enhances both women's and men's fitness. (25th July 2022) - Hagen, Renée V.; Knorr, Delaney A.; Li, Sally; Mensing, Ashley; Scelza, Brooke A.
Abstract: We argue that Benenson et al. need to consider not only sex differences in the effects of care on offspring survival but also in age-specific fertility when predicting how longevity affects fitness. We review evidence that staying alive has important effects on both women's and men's fitness, and encourage consideration of alternative explanations for observed sex differences in threat responses.